The sexual education teaching guides, the religious contest, and the regulation of sexual normality in Costa Rica, 1985-1998 - Jiménez Bolaños, José Daniel (Historia y Memoria de la Educación, 2021)
The objective of this article is to analyze in historical perspective and through journalistic sources, the development of the writing, discussion, and implementation of the sexual education teaching guides in Costa Rica since 1985. From their very inception they were contested by the country’s main religious authorities. This religious challenge gave rise to an outburst of public opinion, with voices for and against the clergy’s intervention in the development of the teaching guides. The tug of war between state efforts and ecclesiastical refusal led to a reformulation of the guidelines, with changes in their content that conferred to them an approach that was less secular and closer to Christian dogmas. This process of polarization evidenced the two different projects that coexisted in the country in the construction and regulation of sexual normality in the classroom, the point of contention being the predominance otherwise of the religious axes. The guides had a limited effect at the educational level..